ROMAN CATHOLIC CHURCH AND POLISH SOCIETY IN THE SECOND HALF OF THE 20TH TO THE BEGINNING OF THE 21st CENTURY: CULTURAL RELIGIOUS ASPECT - BURAVSKY , Olexandr; KOZLOVETS, Mykola (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
Among the pressing issues of modern Polish society development, cultural and religious problems hold a prominent place. Traditionally, the cultural and religious realm has been the field of activity for the Roman Catholic clergy, which has achieved significant success in this domain. This article focuses on the study of the cultural and religious activities of the Roman Catholic Church (RCC) in the Polish society from the second half of the 20th to the beginning of the 21st century. The research methodology is grounded in the principles of historicism, objectivity, systematicity, and scientific rigor, as well as the utilization of general scientific methods such as analysis and synthesis, induction and deduction, comparison, and generalization, on a socioculteral approach. During the processing of the source base, methods of historical cultural and analytical analysis, criticism, and periodization, classification and typologization have been applied. The scientific novelty consists in the fact that a new conceptual vision of the cultural and religious activities of the RCC in the Polish society in the second half of the 20th – to the beginning of the 21st centuries has been proposed, its main directions have been outlined, and its impact on society and on the rise of the national consciousness of the Poles has been characterized. Conclusions.Throughout the second half of the 20th to the beginning of the 21st century, the RCC served as a bearer of national consciousness, preserving language, cultural traditions, and historical memory. The cultural and religious influence of the church on Polish society was significant in shaping moral values. Its influence on education, art, and public behaviour contributed to the maintenance of traditional values and the establishment of ethical norms. Religious education, the Roman Catholic press, became key factors in the cultural and religious life of the Polish society. The RCC adapted to new social realities. It maintained its position in the spiritual life of society while also seeking answers to new challenges and aiming at becoming a modern centre of spirituality and moral improvement. It is argued that amidst the social changes at the beginning of the 21st century, brought about by the fall of the communist regime, there was also a decline in popular support for the church. Keywords: Roman Catholic Church, Polish society, Republic of Poland, cultural religious activity, religious education.